Akad Wakalah Menjadi Penyebab Pembiayaan Murabahah Bergeser Dari Transaksi Jual Beli Menjadi Transaksi Jasa - Azis, Abdul; Muslim, Mochamad Bukhori; Hidayah, Nur (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2020)
This paper examines the wakalah contract as the cause of the shift of murabaha  financing from buying and selling transactions to service transactions. Analysis of wakalah legal norms with normative philosophical approaches, normative juridical and empirical juridical. The wakalah contract given by Islamic banks absolutely to customers to make purchases has caused murabaha  financing to shift from buying and selling transactions to service transactions, because the customer has acted for and on behalf of himself in purchasing goods from suppliers, while the money transferred by the bank sharia to customers is considered as borrowed money. A wakalah contract that does not have any effect on transactions on customers in purchasing goods from suppliers, cannot be called wakalah but has the effect of transferring money from Islamic banks to customers as service transactions